Socio-Religious Practices of the Asy-Syahadatain Congregation (Journal Intellectual Sufism Research (JISR), 2023)
This qualitative research focuses on the description of how the social and religious practices of the congregation of the Asy-Syahadatain tarekat make them unique compared to other tarekat. Observation was conducted in Munjul Village and Asy-Syahadatain Mosque Panguragan-Cirebon. Data collection was supported by in-depth interviews with a number of informants. The research found that there are practices that characterise the congregation of this order, namely tawasulan, grave pilgrimage, kliwonan, nazhaman, and white clothes. All of these practices are considered as a form of suluk to get closer to the Creator. Meanwhile, the all-white clothing in every ritual is a reminder that eventually humans will finish with life and enter the barzakh carrying good deeds. The congregation believes that all the practices taught by the teachers and murshids are teachings that are connected to the Prophet Muhammad.